Hepatitis Bs-antigen among blood donors in Ankara - Kanra, Tekin; Pırnar, Aysel (The Turkish Journal of Pediatrics, 1979)
The incidence of HBs Ag was studied by immunoelectroosmophoresis (I E O P) in 4100 commercial and volunteer blood donors in the Hacettepe University Blood Bank in Ankara. The overall prevalence of HBs Ag was 5 %